Systems Thinking for Understanding Sustainability? Nordic Student Teachers' Views on the Relationship between Species Identification, Biodiversity and Sustainable Development - Irmeli Palmberg; Maria Hofman-Bergholm; Eila Jeronen; Eija Yli-Panula (MDPI AG, 2017)
Sustainability is a complex concept including ecological, economic and social dimensions, which in turn involve several aspects that are interrelated in a complex way, such as cultural, health and political aspects. Systems thinking, which focuses on a system's interrelated parts, could therefore help people understand the complexity of sustainability. The aim of this study is to analyse student teachers' level of systems thinking regarding sustainability, especially the ecological dimension, and how they explain the relationship between species identification, biodiversity and sustainability. Nordic student teachers (N = 424) participated in a questionnaire and their open answers were content-analysed and categorised. The results indicate the student teachers' low level of systems thinking regarding ecological sustainability. About a quarter of them (25.4%) had a basic level including interconnections (13.7%), additional feedback (8.9%) and also behavioural aspects (2.8%), but none of them reached an intermediate or advanced level. The low level of systems thinking could be explained by two main factors: (1) Systems thinking has not been used as an educational method of developing understanding of sustainability in teacher education programmes; and (2) systems thinking is also a result of life experiences; the older ones showing more systems thinking than the younger ones. Therefore, elementary forms of systems thinking should be an educational method already in primary education.